Strategies for enhancing the understanding of Islam in the media - Yousif, Ahmed F. (Association of Muslim Social Scientists of North America, 2011)
During the last two decades, the world witnessed a meteoric rise in the role played by the media in influencing human perceptions of other people, places, and things. This tremendous influence has had both beneficial and detrimental consequences for individuals and communities across the globe. Muslims have experienced firsthand the harmful impact of the media and its ability to negatively influence public opinion. How has such a state of affairs come about? Why is Islam so misunderstood in the global media, and more importantly, how can this situation be remedied? This paper will examine some of the reasons for the media’s misunderstanding of Islam, first in the Western world and second in the Muslim world. Subsequently, it will propose various strategies for enhancing the Western and Muslim media’s understanding of Islam.